High and intermediate-resolution spectroscopy of Be stars : An atlas of Hγ, He I 4471 and Mg II 4481 lines - Chauville, J. (2001)
The definition of Be stars (Jaschek et al. 1981) as non-supergiant B stars which at least once have shown some emission in the Balmer lines implies a vast phenomenology whose characteristics, the evolution of their understanding and the questions which still remain open have been widely reviewed in the last five IAU colloquia and symposia on these stars (Slettebak 1976; Jaschek & Groth 1982; Slettebak & Snow 1987; Balona et al. 1994; Smith et al. 2000). The outstanding physical problems related to them can roughly be summarized into two groups of global questions: a) what is the nature of the central stars and when does the Be phenomenon occur during their evolutionary span?; b) what is the structure of their circumstellar envelopes (CE) and how are they produced?